TUTURAN SARKASME PADA ANAK-ANAK JOKI TO’I DALAM KOMUNITAS PECINTA PACUAN KUDA DI KABUPATEN BIMA - Adiman, Andri; Burhanuddin, Burhanuddin; Saharudin, Saharudin (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This research based on an interest in sarcasm in the community of horse racing lovers in Panda, Palibelo subdistrict, which is very cruel compared to sarcasm in the community in general. The aim of this research is to discover the forms and functions of sarcasm in this community. This research used a qualitative approach with data collection methods, namely the listening method through note-taking techniques, skilful involvement, free folding and skill methods through face-to-face techniques. The result of this research show that the community of horse racing fans useed sarcasm as a means to motivate each other. In addition, in the sarcasm speech used by the horse lover community in Panda village, meanwhile the general function of this study provides information that coarse language is not only bad in social life, there are also positive values contained in it, that is strengthen the sense of brotherhood in community life.